2014
DOI: 10.1371/journal.pone.0111269
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Associated with Erectile Dysfunction Based on Cross-Sectional and Genetic Analyses

Abstract: Erectile dysfunction (ED) is a global disease affecting a large number of people. Some studies have found a relationship between low-grade inflammation and ED. We hypothesized that the immune system might play a key role in the outcome of ED. Five immune agents (C3, C4, IgA, IgM, and IgG) were collected based on the Fangchenggang Area Male Health and Examination Survey (FAMHES), using methods of a traditional cross-sectional analysis. Our results repeated the significant association between ED and metabolic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…A study about five immune agents (IgG, IgM, IgA, C4, and C3) was collected on the basis of the Fangchenggang Area Male Health and Examination Survey (FAMHES)and methods of traditional cross-sectional analysis were used. However, there was no clear relationship between ED risk in the baseline analyses and the tested indexes (C3: P = 0.737) (Chen et al, 2014). Another study on sexual dysfunction in male schizophrenia showed that correlation between two polymorphisms in the genes for the DRD2 and scores on questionnaires for erectile and sexual dysfunction were studied.…”
mentioning
confidence: 96%
“…A study about five immune agents (IgG, IgM, IgA, C4, and C3) was collected on the basis of the Fangchenggang Area Male Health and Examination Survey (FAMHES)and methods of traditional cross-sectional analysis were used. However, there was no clear relationship between ED risk in the baseline analyses and the tested indexes (C3: P = 0.737) (Chen et al, 2014). Another study on sexual dysfunction in male schizophrenia showed that correlation between two polymorphisms in the genes for the DRD2 and scores on questionnaires for erectile and sexual dysfunction were studied.…”
mentioning
confidence: 96%
“…As described in our previous studies 27 , 28 , the FAMHES project was carried out from September to December 2009, and involved a routine physical examination at the Medical Center in Fangchenggang First People’s Hospital. The sample comprised 4303 non-institutionalized Chinese men aged 17 to 88 years old, who were from the Fangchenggang area of Guangxi, China.…”
Section: Methodsmentioning
confidence: 99%
“…The blood samples were centrifuged within 15–25 min, and stored at −80 °C. Further details are available in our previous reports 27 29 .…”
Section: Methodsmentioning
confidence: 99%
“…After a comprehensive demographic and health survey, data from 3593 participants in the form of interviews were collected. The response rate was 83.5% [ 24 ]. Written informed consent was obtained for all participants and their guardians.…”
Section: Methodsmentioning
confidence: 99%
“…The C3 , C4 , CRP , IgA , IgM , and IgG levels were detected with electrochemiluminescence immunoassays and immunoturbidimetric methods. All details were presented in our previous publications [ 23 24 , 27 ].…”
Section: Methodsmentioning
confidence: 99%